ACCESS TO OUTPUT MARKET BY SMALL FARMERS: THE CASE OF PUNJAB, PAKISTAN - U. I. Ahmed; L. Ying; M. K. Bashir; M. Abid; E. Elahi; M. A. Iqbal (Journal of Animal and Plant Sciences, 2016)
Transport infrastructure in Pakistan is still a problem for rural people to access output markets. This study aims to identify the ways to improve access of small farming households to output markets. To achieve this aim, specific objectives are: to find out the determinants of small farmers’ access to output markets; and to assess impact of these factors on farmers’ income. For this purpose, primary data from 576 households were collected from twelve districts of the Punjab province. To achieve the first objective, logistic regression was used as the dependent variable is a binary variable. For second objective, the dependent variable was in a continuous variable which guided towards the application of a OLS model. The results of the study revealed that the education, cost of transportation, distance from farm to market and access to market information were the factors which determined the accessibility of farmer to output market. A significant impact of these factors was found on the income of small farmers. The study suggests that the transportation facilities, market infrastructure and flow of market information should be improved.
Keywords: Farm households; Agriculture markets; Market information; Access to market; Transport; Transportation cost; Extension services